Probiotics and postbiotics from Southeast Asian traditional fermented foods highlight functional potential in Malaysia - Sakina, Shahabudin; Mohd Faizulnazrie, Masri; Nina Suhaity, Azmi (Hibiscus Publisher, 2025)
Fermented foods are essential in Southeast Asia's culinary and cultural landscapes, providing nutrition, preservation, and microbial diversity. Beyond their traditional significance, these foods include beneficial probiotics and metabolic by-products, known as postbiotics, that improve food functionality and human health. This review compiles recent research on the probiotic diversity and postbiotic potential of fermented foods from Southeast Asia, with a focus on traditional Malaysian variations such as budu, tempoyak, belacan, cincalok, tapai, pekasam, and pickled maman. It covers the most common microbial species, fermentation substrates, and bioactive metabolites in the fermented foods, while also highlighting recently discovered postbiotic components such as exopolysaccharides, peptides, and short-chain fatty acids. Despite these advantages, Malaysian traditional fermented foods have received minimal research, particularly in metabolomic characterization and clinical validation. Omics tools integration, safety assessment, and the valuation of local probiotic strains for functional food innovation will be beneficial in the next steps for fermentation science in Malaysia.